Local and international prospective teachers’ perception on collaborative learning - Alimin Adi Waloyo; Santi Prastiyowati; Ummu Artha Tsary Rumalessin (Universitas Muhammadiyah Malang, 2020)
Many EFL learners show higher achievement, feel more satisfied with their learning experiences, and display higher motivation to develop their English when they are engaged in collaborative learning. However, others display lack of contribution, low commitment, bad time management, and passive membership during the collaboration with other learners. In this case, teachers’ role is paramount to provide constructive feedback and supervise the learners to eliminate these potential issues. This research was conducted by involving both local and international EFL students in Indonesian context and addressed how local and international students of English Education at University of Muhammadiyah Malang (UMM) perceived group assignment. The research involved 7 international (Thai) students and 7 local (Indonesian) students, studying at English Education of UMM, academic year 2015. The instruments were questionnaires (likert scale and open-ended questions) and interview, which were anayzed using both quantitavie and qualitative method.This mixed method helped the researchers obtain comprehensive data and required information. The classified data was analyzed by calculating each item using descriptive statistic for close ended questions and descriptive interpretation for open ended questions and interview items. The investigation found that the students completely realized the positive effects of group work advancing their academic performance and developing their personal attitudes. Therefore, applying collaborative learning as a part of teaching activity in EFL context is highly encouraged to help learners perform better both academically and individually.